Can Investment Shocks Explain the Cross Section of Equity Returns? - Garlappi, Lorenzo; Song, Zhongzhi (Management Science, 2017)
Using two macro-based measures and one return-based measure of investment-specific technology (IST) shocks, we find that over the 1964–2012 period, exposure to IST shocks cannot explain cross-sectional return spreads based on book-to-market, momentum, asset growth, net share issues, accrual, and price-to-earnings ratio. Only one of the two macro-based measures can explain a sizable portion of the value premium over the longer 1930–2012 period. We also find that the IST risk premium estimates are sensitive to the sample period, the data frequency, the test assets, and the econometric model specification. Impulse responses of aggregate investment and consumption indicate potential measurement problems in IST proxies, which may contribute to the sensitivity of IST risk premium estimates and the failure of IST shocks to explain cross-sectional returns. This paper was accepted by Neng Wang, finance.